The Influence of the Construction of Sports Tourism Towns on the Psychological Status of Local Residents - Ziwen Wang; Cangli Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Understand the mental health status of residents aged 15 and above in a sports tourism town, the research aimed was to check the influence of the construction of sports tourism towns on the psychological status of local residents. For this purpose, a multistage random sampling method was used to conduct a questionnaire survey on the mental health status of 3295 local residents, and the data were processed and analysed using SPSS 19.0 software. Of the 3295 residents surveyed, 410 had poor mental health, accounting for 12.44% of the total number of people surveyed. The total score of SCL-90 of residents in local provinces is lower than the national norm (t=14.647, P=0.000), and the scores of various factors of SCL-90 of residents in local provinces are significantly higher than the national norm (P=0.000). The correlation analysis results showed that the total score of happiness was negatively correlated with the total score of SCL-90 (r=1.883, P<0.01), and the psychological awareness and hygiene score was also negatively correlated with the total score of SCL-90 (r=0.598, P<0.01). The results of multiple linear regression analysis showed that the factors that entered the regression equation included total happiness score, marital status, family life, satisfaction with the environment, whether life was monotonous, personality, participation in gatherings, and whether the three generations of the family had mental illness, according to the size of the standard regression coefficient, the most influential factor is the total score of happiness(β= 0.426), followed by marital status(β= 0.097).The mental health status of residents in the local province is not optimistic, the total score of happiness, marital status, family life, satisfaction with the environment, whether life is monotonous, and personality have varying degrees of impact on residents' mental health. Necessary intervention measures should be taken to improve their mental health based on their influencing factors. The research could help to application of targeted interventions and community-based programs to enhance the mental well-being of local residents in sports tourism towns, fostering sustainable development and social harmony. The research limitations and future directions were also discussed.